Radiation Detection and Measurement - Knoll, Glenn F. (John Wiley & Sons, 2000)
Whilst maintaining its comprehensive depth in coverage, this edition includes up-to-date information, including sections on digital pulse processing, compound semiconductor detectors and recent detector developments.